ANALISIS KINERJA KEUANGAN BANK PERKREDITAN RAKYAT DI WILAYAH MALANG RAYA - Popy Dwi Alinda; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2018)
This study aims to determine the financial performance of rural banks in Malang Raya based on capital adequacy, asset quality, profitability and liquidity. Data collection in this study used documentation techniques obtained from the financial statements taken from the Financial Services Authority (OJK). Data analysis used is descriptive with quantitative approach. Based on the results of the analysis that has been done shows that there is 1 BPR that does not reach the standard value determined by Bank Indonesia is BPR Putra Arta Dewata with a value of 5%, and there are 5 BPR that has shown that the BPR is superior in ratios of BPR Pujon Jaya Makmur, BPR Artha Kanjuruhan Malang Regency, BPR Eka Dana Utama, BPR Armindo Kencana and BPR Tripakarti Dhanatama.Keywords: BPR, capital adequacy, asset quality, profitability, liquidity